Presupuesto de la liga cantonal de Puebloviejo periodo 2020-2021. - Quinto Nieto, Robín Rider (2022)
In the present case study, an analysis of the budget granted by the regional coordination area 8 of the Ministry of Sport of Ecuador to the Cantonal Sports League of Puebloviejo (LCDP) in the period 2020-2021, in order to evaluate how the allocation of economic resources was managed, after the cut of the budget by the Ecuadorian government, due to the economic crisis caused by the covid-19. To evaluate the LCDP's administration of the budget, the use of the deductive methodology was necessary, through the review of reports, element that allowed to evaluate the budgetary indicators and have a clear view of the current situation of the institution with regard to the administration of the economic resources allocated by the state. To evaluate the LCDP's administration of the budget, the use of the deductive methodology was necessary, through the review of reports, element that allowed to evaluate the budgetary indicators and have a clear view of the current situation of the institution with regard to the administration of the economic resources allocated by the state.